Avalia????o da capacidade funcional e respirat??ria de mulheres com obesidade m??rbida, antes e ap??s a perda de peso pela cirurgia bari??trica - Campos, Elaine Cristina de (2014)
Objective. To evaluate respiratory muscle strength, lung function, functional capacity, and the level of habitual physical activity morbidly obese women before and after undergoing bariatric surgery; and investigate the relationship of these variables with the changes in body composition and anthropometric after weight loss. Method. 24 morbidly obese women were evaluated in preoperative screening in the Mandaqui Hospital Complex, as your lung function by spirometry, respiratory muscle strength through pressure manometry, functional capacity through incremental test Shuttle, body composition by bioelectrical impedance, anthropometry and habitual physical activity by the Baecke, 2 weeks before and 4-6 months after bariatric surgery. Results: The spirometry showed a significant increase of 160 ml in SVC (p = 0.01) 7% of predicted, 550 ml in VRE (p = 0.01), 290 ml in FVC (p = 0, 02) 6% predicted FEV1 and 250 ml (p = 0.02) and 6% predicted, a significant reduction in IC 490 ml (p = 0.04); was observed significant increase of 10 cmH2O MIP (p = 0.01) and functional capacity, 72 meters from distance in incremental shuttle test (p <0.0001); there were significant changes between anthropometric variables and body composition (p <0.0001), but not at the level of physical activity, they remained sedentary. They also found correlations between lean mass and fat mass percentages with the VRI and VRE. Conclusion. These data indicate that possibly changes in body composition and anthropometric variables have influenced directly and positively functional capacity and pulmonary function of these women, however, no influence on the lifestyle, even after marked weight loss after bariatric surgery.